2014
DOI: 10.1159/000365844
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Dysfunction: How Much Longer Will It Be Controversial?

Abstract: Background: Motility disorders of the biliary tree [biliary dyskinesia, including both gallbladder dysfunction (GBD), and sphincter of Oddi dysfunction] are difficult to diagnose and to treat. Summary: There is controversy in the literature in particular regarding the criteria that should be used to select patients for cholecystectomy (CCY) in cases of suspected GBD. The current review covers the history, diagnosis, and treatment of GBD. Key Messages: Only >85% of patients with suspected GBD have relief follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 60 publications
1
10
0
5
Order By: Relevance
“…В последние десятилетия отмечена устойчивая тенденция к росту заболеваемости хроническим холециститом. Данная патология встречается не только в зрелом, но и в молодом возрасте [4,5,6,7]. Современный подход к медико-социальной проблеме больных подразумевает комплекс мероприятий, направленных на предупреждение развития осложнений [8,9,10].…”
Section: Discussionunclassified
“…В последние десятилетия отмечена устойчивая тенденция к росту заболеваемости хроническим холециститом. Данная патология встречается не только в зрелом, но и в молодом возрасте [4,5,6,7]. Современный подход к медико-социальной проблеме больных подразумевает комплекс мероприятий, направленных на предупреждение развития осложнений [8,9,10].…”
Section: Discussionunclassified
“…A few meta-analyses on the existing outcome after LC based on CCK-cholescintigraphy or ultrasound scans for ABP patients were performed [24][25][26][27], and it was indicated that the use of EF to select patient with suspected ABP is not supported, even though the symptom is more significantly relived than nonoperative therapy; consequently, randomized clinical trials are on demand [24,25,28,29]. To standardize the trials and make the outcomes of different trials comparable, a protocol was recommended based on 0.02 µg/kg sincalide over 60 min with normal EF specified ≥ 38% [30].…”
Section: Introductionmentioning
confidence: 99%
“…GBs can suffer from a variety of disease such as gallstones, cholecystitis, acalculous gallbladder disease, biliary dyskinesia and gallbladder cancer [2,15,29]. The disease can alter passive and active biomechanical properties of GB wall [1,4,7,12,25]. Thus, the biomechanical properties of GB wall should be valuable to diagnosis of GB diseases.…”
Section: Introductionmentioning
confidence: 99%